Development of a Test Tube Automatic Sorting Storage Device After Completion of Inspection - Zhao Peng; Farra A. Jumuddin (Wolters Kluwer Medknow Publications, 2024)
Objective: To develop an automatic test tube classification and storage device that sorts test tube boxes by detecting the box height and test tube cap color, improving laboratory efficiency and accuracy. Methods: An upper computer uses a No. 1 push rod to allocate test tube boxes to specific branch conveyor belts based on initial sorting criteria. Further sorting is done by the No. 2 push rod, which places boxes into adjustable slots within a seven-layer elevating storage system, categorizing them by day through height adjustment to match the conveyor belt. Conclusion: This invention automates test tube sorting and storage, aiding medical staff in quickly and accurately locating test tubes post-inspection.